22nd meeting of the European Society of Gynaecological Oncology (ESGO 2021) report. Issue 11 (5th October 2022) - Razumova, Zoia; Bizzarri, Nicolò; Pletnev, Andrei; Theofanakis, Charlampos; Selcuk, Ilker; van der Steen-Banasik, Elzbieta; Gonzalez Martin, Antonio; Persson, Jan
Abstract : This is a report from the 22nd Meeting of the European Society of Gynaecological Oncology, held October 23–25, 2021. The 3-day event offered an educational experience covering the major scientific and clinical advances in gynecological oncology. The Congress program included different session formats, including guidelines updates and state-of-the-art lectures. This article provides an overview of the main Congress activities as well as of the most important studies that were presented at the event for the first time.